The Madura Foot: A case of eumycotic mycetoma on histopathology - Dr. D.S. Jadhav; Dr. Anuja U. Paul; Dr. B. D. Baste; Dr. A. G. Valand (Tropical Journal of Pathology and Microbiology, 2017)
Madura foot is a deep mycosis commonly seen in tropical and subtropical countries such as India. It is caused by two groups of organisms, bacteria belonging to the group of Actinomycetes and the true mycetes named eumycetes. The incidence is more common in agricultural workers. Generally these lesions were present on foot & shows presence of induration, fibrosis and minimal discharge from sinuses. Though culture remains the gold standard diagnostic test histopathology plays important role in the early diagnosis and definitive treatment of these cases.